Tetrathiomolybdate Treatment Attenuates Bleomycin-Induced Angiogenesis and Lung Pathology in a Sheep Model of Pulmonary Fibrosis - Derseh, Habtamu B.; Perera, Kopiyawaththage U. E.; Dewage, Sasika N. Vithana; Stent, Andrew; Koumoundouros, Emmanuel; Organ, Louise; Pagel, Charles N.; Snibson, Ken J. (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis (IPF) is a progressive chronic lung disease characterized by excessive extracellular matrix (ECM) deposition in the parenchyma of the lung. Accompanying the fibrotic remodeling, dysregulated angiogenesis has been observed and implicated in the development and progression of pulmonary fibrosis. Copper is known to be required for key processes involved in fibrosis and angiogenesis. We therefore hypothesized that lowering bioavailable serum copper with tetrathiomolybdate could be of therapeutic value for treating pulmonary fibrosis. This study aimed to investigate the effect of tetrathiomolybdate on angiogenesis and fibrosis induced in sheep lung segments infused with bleomycin. Twenty sheep received two fortnightly infusions of either bleomycin (3U), or saline (control) into two spatially separate lung segments. A week after the final bleomycin/saline infusions, sheep were randomly assigned into two groups (n=10 per group) and received twice-weekly intravenous administrations of either 50 mg tetrathiomolybdate, or sterile saline (vehicle control), for six weeks. Vascular density, expressed as the percentage of capillary area to the total area of parenchyma, was determined in lung tissue sections immuno-stained with antibodies against CD34 and collagen type IV. The degree of fibrosis was assessed by histopathology scoring of H&E stained sections and collagen content using Masson’s trichrome staining. Lung compliance was measured via a wedged bronchoscope procedure prior to and seven weeks following final bleomycin infusion. In this large animal model, we show that copper lowering by tetrathiomolybdate chelation attenuates both bleomycin-induced angiogenesis and pulmonary fibrosis. Moreover, tetrathiomolybdate treatment downregulates vascular endothelial growth factor (VEGF) expression, and improved lung function in bleomycin-induced pulmonary fibrosis. Tetrathiomolybdate also suppressed the accumulation of inflammatory cells in bronchoalveolar lavage fluid two weeks after bleomycin injury. The molecular mechanism(s) underpinning copper modulation of fibrotic pathways is an important area for future investigation, and it represents a potential therapeutic target for pulmonary fibrosis.